2008
DOI: 10.1063/1.2889496
|View full text |Cite
|
Sign up to set email alerts
|

Application of channeling-enhanced electron energy-loss spectroscopy for polarity determination in ZnO nanopillars

Abstract: Polarity in noncentrosymmetric crystals has been shown to affect a number of critical material properties. Here, we demonstrate the application of channeling-enhanced electron energy-loss spectroscopy for the determination of Zn polarity in ZnO nanopillars grown by the chemical vapor deposition method and detail important experimental parameters for the application of this technique. We also confirm ZnO polarity using the more common convergent beam electron diffraction technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Overall, the issue of polarity in the field of ZnO nanostructures have been reported depending on the polarity of the ZnO nucleation surface ,,,, and investigated regarding their polarity itself. The physical and chemical vapor deposition techniques typically results in the formation of Zn-polar ZnO NRs ,,, or nanostructures following the catalyst-free or self-induced approaches, , regardless of the polarity of the nucleation surface. Even on O-polar ZnO nucleation surfaces, extended defects like inversion domain boundaries are commonly formed to reverse the polarity of ZnO NRs in favor of the Zn-polarity, owing to aluminum surfactant effects. , In contrast, Consonni et al recently showed that O-polar ZnO NRs can be formed by using CBD and that their structural uniformity can thoroughly be controlled on patterned ZnO single crystals by electron beam lithography (EBL) .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the issue of polarity in the field of ZnO nanostructures have been reported depending on the polarity of the ZnO nucleation surface ,,,, and investigated regarding their polarity itself. The physical and chemical vapor deposition techniques typically results in the formation of Zn-polar ZnO NRs ,,, or nanostructures following the catalyst-free or self-induced approaches, , regardless of the polarity of the nucleation surface. Even on O-polar ZnO nucleation surfaces, extended defects like inversion domain boundaries are commonly formed to reverse the polarity of ZnO NRs in favor of the Zn-polarity, owing to aluminum surfactant effects. , In contrast, Consonni et al recently showed that O-polar ZnO NRs can be formed by using CBD and that their structural uniformity can thoroughly be controlled on patterned ZnO single crystals by electron beam lithography (EBL) .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we devote the final section of the present work to illustrate possible polarity inversions in nanostructured semiconductor materials, discussing a few examples of inversion boundaries, which eventually allow a smart manifold functionalization of the Polarity-Driven Growth of Vertical Nanowires. While semiconductor NWs have extensively been studied systems over 48 Poole et al, 49 Gao et al 50 → SAG B (P) Algra et al, 51 Dalacu et al, 52 Calahorra et al 53 → particle-assisted GaN A (Ga) Schuster et al, 33 Bengoechea-Encabo et al 54 → SAG B (N) Fernańdez-Garrido et al, 55 Bertness et al, 56 Schuster et al 57 → particle-assisted Muβëner et al 58 → spontaneous growth InN A (In) Wang et al 59 → spontaneous growth B (N) Stoica et al, 60 Chang et al, 61 Wang et al 59 → spontaneous growth ZnO A (Zn) Baxter et al, 62 Sallet et al, 63 Utama et al, 64 Guillemin et al, 65 Sun et al, 66 Nicholls et al 67 → spontaneous growth Scrymgeour et al, 68 Perillat-Merceroz et al, 69 Consonni et al 70 → SAG Jasinski et al 71 → particle-assisted B (O) Guillemin et al 72 → spontaneous growth Consonni et al 70 → SAG Sallet et al 63 → particle-assisted Figure 3. Intrinsic parameters of the binary compounds analyzed, such as the ratio between the constituent sizes (r b /r a ), including the cases of ionic (a), covalent (b), and atomic radius, and the ionic character of the compound showing the electronegativity for each constituent, χ, along with the difference in electronegativity for every considered compound (d), calculated following Pauling's expression (more details provided in the Supporting Information).…”
mentioning
confidence: 99%
“…The crystallographic polarity can be determined using several methods, including low-energy electron diffraction (LEED), reflection high-energy electron diffraction (RHEED), X-ray diffraction (XRD), , X-ray photoelectron diffraction (XPD), convergent beam electron diffraction, , Auger electron spectroscopy, , and electron energy-loss spectroscopy . None of these methods, however, can be employed to determine the surface polarity of SiC; because they characterize SiC through interactions between incident electrons and a long-range-ordered atomic arrangement of the substrate, they cannot be used to analyze only the surface layer of the SiC wafers.…”
Section: Introductionmentioning
confidence: 99%